The critical power concept and bench press: Modeling 1RM and - Morton, R. H.; Redstone, M. D.; Laing, D. (International Journal of Exercise Science, 2014)
Introduction: We demonstrate application of the 3-parameter critical power (CP) model derived for cycling and running, to performance at bench press exercise. We apply the model to both performance of a single repetition maximum (1RM) and multiple repetitions (reps) to failure at different submaximal weights. Methods: Sixteen weight-trained young adult male participants each performed a modified YMCA 1RM test and four sets of fixed cadence reps to failure at different sub-maximal weights. The CP model equation takes the form: n = ALC/(m - CL) + ALC/(CL - Lmax,), where n is the number of reps to failure and m is the sub-maximal weight lifted (kg). ALC is the anaerobic lift capacity (kg), CL is the critical lift (the maximal continuous aerobic ability at bench pressing, kg), and Lmax is the maximal `instantaneous` lift (kg). Results: The 3- parameter critical power model fits recorded reps to failure very well in almost all subjects (0.9556 < R2 < 0.9999), and provides estimates of the three model parameters for each individual. CL was not significantly different from zero, suggesting that the aerobic energy contribution to short duration bench press sessions is negligible. When used to estimate 1RM for each subject, the CP model produces estimates significantly greater (p < 0.05) than those obtained using the YMCA procedure. Conclusion: The CP concept can be used to accurately model bench press reps to failure at different submaximal weights in a homogeneous group of individuals. Prediction of 1RM is possible, but caution should be exercised in interpreting and using the prediction.